Lateral pressure-mediated protein partitioning into liquid-ordered/liquid-disordered domains. Issue 13 (26th February 2016) - Frewein, Moritz; Kollmitzer, Benjamin; Heftberger, Peter; Pabst, Georg
Abstract : We have studied the contributions of stored elastic energies in liquid-ordered (Lo) and liquid-disordered (Ld) domains to transmembrane proteins using the lateral pressure concept. Abstract : We have studied the contributions of stored elastic energies in liquid-ordered (Lo) and liquid-disordered (Ld) domains to transmembrane proteins using the lateral pressure concept. In particular we applied previously reported experimental data for the membrane thickness, intrinsic curvature and bending elasticities of coexisting Lo/Ld domains to calculate whether proteins of simple geometric shapes would preferentially diffuse into Lo or Ld domains and form oligomers of a certain size. For the studied lipid mixture we generally found that proteins with convex shapes prefer sorting to Ld phases and the formation of large clusters. Lo domains in turn would be enriched in monomers of concave shaped proteins. We further observed that proteins which are symmetric with respect to the bilayer center prefer symmetric Lo or Ld domains, while asymmetric proteins favor a location in domains with Lo/Ld asymmetry. In the latter case we additionally retrieved a strong dependence on protein directionality, thus providing a mechanism for transmembrane protein orientation.